2007
DOI: 10.1542/peds.2007-1010g
|View full text |Cite
|
Sign up to set email alerts
|

Is Family History a Useful Tool for Detecting Children at Risk for Diabetes and Cardiovascular Diseases? A Public Health Perspective

Abstract: Several studies indicate that the risk for type 2 diabetes or cardiovascular disease is detectable in childhood, although these disorders may not emerge until adulthood. In addition, type 2 diabetes and cardiovascular disease seem to share risk factors, including obesity and dyslipidemia, and might even share etiology, which has important implications for screening and prevention strategies for both diseases. Primary prevention, in particular, has gained importance because the results of major randomized, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 98 publications
1
54
0
7
Order By: Relevance
“…Entre ellos se pueden encontrar los antecedentes familiares de dislipidemia e infarto agudo de miocardio (IAM) 2,4,5 , y también la obesidad que, debido a que ha aumentado su frecuencia, se ha constituido en uno de los principales factores de riesgo, tanto en adultos 6,7 como en niños y adolescentes [7][8][9] .…”
Section: Introductionunclassified
“…Entre ellos se pueden encontrar los antecedentes familiares de dislipidemia e infarto agudo de miocardio (IAM) 2,4,5 , y también la obesidad que, debido a que ha aumentado su frecuencia, se ha constituido en uno de los principales factores de riesgo, tanto en adultos 6,7 como en niños y adolescentes [7][8][9] .…”
Section: Introductionunclassified
“…Although we could not validate reported history of diabetes and CVD with medical records, evidence suggests that family history of diabetes and major CVD events are reported fairly accurately, because they are serious, but not stigmatised, diseases with clear case definitions [3,28]. Family history of diabetes may have been underreported because of under diagnosis [3], which may have led to underestimation of the true association. Mothers of the PIAMA children completed most questionnaires (85%), which is likely to explain the higher number of unknowns and missing reports of disease cases in the fathers' lineage.…”
Section: Discussionmentioning
confidence: 90%
“…socioeconomic position and health behaviours [1]. The association of cardiovascular disease (CVD) in first-or second-degree relatives with the presence of risk factors for atherosclerosis, such as high cholesterol and BP, in children has been described [2,3]. Other studies showed that familial aggregation of type 2 diabetes also relates to the presence of cardiometabolic abnormalities in children [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple way to detect any risk for both diseases is to examine the family history. Family history can be part of the approach for screening children at risk of diabetes and cardiovascular disease and its investigation must include campaigns to reduce their risk factors 25 .…”
Section: Cimadon Et Al Dietary Habits In Students From Bento Gonçalvesmentioning
confidence: 99%